2021
DOI: 10.1016/j.diabres.2020.108562
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the newer oral hypoglycemic agents in patients with T2DM during Ramadan: A systematic review and meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…Gad et al elucidated similar outcomes that favor the efficacy of SGLT-2 inhibitors, GLP-1 agonists, and DPP-4 inhibitors; however, the study does not ascertain the efficiency of newer oral hypoglycemic in the hierarchy of least hypoglycemic events. [9]Furthermore, the meta-analysis by Gad et al approves both lixisenatide and liraglutide for fasting diabetic patients in Ramadan like our study. Similarly, a meta-analysis by Gray et al…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Gad et al elucidated similar outcomes that favor the efficacy of SGLT-2 inhibitors, GLP-1 agonists, and DPP-4 inhibitors; however, the study does not ascertain the efficiency of newer oral hypoglycemic in the hierarchy of least hypoglycemic events. [9]Furthermore, the meta-analysis by Gad et al approves both lixisenatide and liraglutide for fasting diabetic patients in Ramadan like our study. Similarly, a meta-analysis by Gray et al…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, it also highlighted that incretin-based mimetics manifest 1.5 times lesser hypoglycemic events [8]. Likewise, a recent meta-analysis demonstrated that DPP-4 and glucagon-like peptide (GLP-1) agonist therapy significantly improves HbA1c levels amongst fasting diabetic patients during Ramadan [9]. Other studies have also shown that Ramadan-focused diabetes education helps create awareness among the population, ensuring a decline in HbA1c levels in fasting patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that the patients from this region were the youngest overall and a high proportion were receiving at least three antidiabetic agents, which may be associate with better glycaemic control overall. The results for HbA 1c and FPG are similar to those observed for newer oral antidiabetic agents (DPP4 inhibitors, SGLT2 inhibitors, GLP-1 receptor agonists) during Ramadan presented in a recent meta-analysis [32].…”
Section: Changes In Hba 1c and Fpgsupporting
confidence: 77%
“…As such, current recommendations advocate that patients with diabetes who wish to fast should discuss the risks and benefits of fasting with their healthcare providers, and make adjustments to the dose, timing and type of medication during Ramadan. Several recent systematic reviews and meta-analyses have shown that the newer glucose-lowering therapies have a lower risk of hypoglycemia during Ramadan 21 . The present meta-analysis showed that Ramadan fasting is associated with a ~0.4% decrease in HbA1c in patients treated with SGLT-2i, which is comparable to the reduction observed with dipeptidyl peptidase-4 inhibitors and glucagon-like peptide 1 receptor agonists during Ramadan fasting 21 , and the incidence of hypoglycemia was lower compared with sulfonylureas.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent systematic reviews and meta-analyses have shown that the newer glucose-lowering therapies have a lower risk of hypoglycemia during Ramadan 21 . The present meta-analysis showed that Ramadan fasting is associated with a ~0.4% decrease in HbA1c in patients treated with SGLT-2i, which is comparable to the reduction observed with dipeptidyl peptidase-4 inhibitors and glucagon-like peptide 1 receptor agonists during Ramadan fasting 21 , and the incidence of hypoglycemia was lower compared with sulfonylureas. Fasting was also associated with minor weight loss in type 2 diabetes mellitus patients taking SGLT-2i, in contrast to the results of a recent meta-analysis showing weight gain during Ramadan 22 .…”
Section: Discussionmentioning
confidence: 99%